Pengaruh Beban Kerja dan Stres Kerja terhadap Kinerja Anggota Satuan lalu Lintas Kepolisian Resor Kota Samarinda - Yeyen Afera; Rinda Sandayani Karhab; Vera Anitra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the influence of workload and work stress on the performance of the Traffic Unit members of the Samarinda City Police Resort. The method used is a quantitative survey by distributing questionnaires to 129 traffic unit members selected from a population of 190 members using the Slovin formula. Data analysis was conducted using SPSS for validity, reliability, and multiple linear regression tests. The results of the study indicate that workload and work stress have a significant impact on the performance of police officers. Well-managed workload and effectively addressed work stress can enhance the performance of the members. The implications of this study emphasize the importance of workload and stress management programs, time management training, and a supportive work environment to improve the performance and well-being of police officers.